Global Analysis of Almost Periodic Solution of a Discrete Multispecies Mutualism System - Hui Zhang; Bin Jing; Yingqi Li; Xiaofeng Fang (Journal of Applied Mathematics)
This paper discusses a discrete multispecies Lotka-Volterra mutualism system. We first obtain the permanence of the system. Assuming that the coefficients in the system are almost periodic sequences, we obtain the sufficient conditions for the existence of a unique almost periodic solution which is globally attractive. In particular, for the discrete two-species Lotka-Volterra mutualism system, the sufficient conditions for the existence of a unique uniformly asymptotically stable almost periodic solution are obtained. An example together with numerical simulation indicates the feasibility of the main result.